Building the Character and Thought Structure of Political Actors based on Pancasila Politics - Ruhadi Ruhadi; Giri Harto Wiratomo (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
The development of a negative stigma against politics today is a reality that occurs in the mindset of society. This is caused by various factors including the thoughts, attitudes, and behavior of political actors. One of them is a politician. The thoughts, attitudes, and behavior of politicians have a significant role in shaping the image of politics in the eyes of society. Currently, there is a lot of negative stigma about politics. There are two theories in politics, namely moral based theories and political theories that ignore the moral conflict between these two theories and there is a tug of war in the current political field in politicians so that two problems are related to the background of the basic thought structure of politicians who are driven to practice praxis. negative politics and efforts to form a political thought structure that is in line with the "Political Value" of the Indonesian nation are interesting issues to study. The method used in this paper is a qualitative approach with the literary study method, based approach, it can be seen that the theories currently developing are political theories that ignore the moral basis and requirements with pragmatism in politics so that it requires the strengthening and construction of the Pancasila political building which is prerequisite. with immorality to displace political theories that are far from moral bases and to eradicate various immoral behavior of politicians today.